The training of cataloguers in Kemerovo State Institute of Culture - L. G. Taranenko; O. Ya. Sakova (Библиосфера)
The 50-year history of the cataloguers training at Kemerovo State Institute of Culture (KemSIC) is considered. The goal of the research is to summarize the experience of machine-readable cataloging training in the framework of specialization “The Library and Information Activity”. The modern characteristic of the educational process in the aspects of cataloging training, based on the principles of technological approach, is presented. The article deals with the main problems of cataloging tasks in the research activities of students and tutors of the Institute. Based on the analysis of documentary sources (scientific, educational), analysis of training experience in KemSIC the following results are obtained: basing on the theory of technological approach to library operations (the author – Dr. of Sciences (Pedagogy) I. S. Pilko) the department of documentary communications technology, cataloging of documents is regarded as a set of technological processes. This approach is used in the model of analytic-synthetic processing of information, promotes universal and professional competences in cataloguing acquired by students, and is used in research activities of students, bachelor’s papers and master’s theses. The relationship of the department of documentary communications technology with the leading library centers of the Russian Federation and libraries of Kuzbass in the field of cataloging testifies to the adaptability of the Kemerovo library school to modern requirements of cataloging training.